METHODOLOGICAL APPROACH IN ESTIMATING THE DEMAND FOR RECREATIONAL SITES - John E. H. J. FoEh (Jurnal Ilmiah Ekonomi Bisnis, 2019)
Basically, there are two main problems faced in the recreation location especially in outdoor. One side, the rate of visiting some tourism objects is still low until now. It raises an assumption that recreation location doesn’t create any opportunity in regional and domestic economy. On the other hand, undervalue of recreation services, based on the willingness to pay caused a very low attractiveness of investment in tourism objects. To solve these problems, one should be able to predict the number of recreation location demand, so that a good planning and development could be implemented in this estimated area. One of the very common methods to calculate this demand is to use the travel cost methods. Many independent variable could be implemented in a multiple linear regression model, depends on the objective of the research. Somehow, a valid data is necessary in the application of statistical and quantitative analysis. Experiences showed a significant result of analysis using this travel cost methods.